O inquérito civil como instrumento de atuação do Ministério Público na defesa dos direitos subjetivos individuais indisponíveis e coletivos - Lacerda, Aloyr Dias (2012)
This thesis aims to analyze the civil investigation, as a tool to be used by Public Attorney to the achievement of their duties-powers, in order to ensure the realization of the unalienable and fundamental rights. Thus, the investigation starts exposing the genesis of the concept of rights, and the various theories developed on the theme, culminating in the adoption of a concept of rights established in a "complex legal situation," or "special permission to use" granted by law. In this view, the rights can be subdivided into three species: performance rights, potestative rights and duties rights (or duties powers). Next, was analyzed the historical development of Public Attorney as an institution that was created as a defender of the law since the pre-democratic period, but that reached full maturity only with the advent of the Constitution of 1988, when its powers were extended and its function guided to the protection of society and the democratic regime. Increased effectiveness of Public Attorney in carrying out its constitutional mission can only be achieved, however, through democratic actions, searching for an effective contact with civil society, to know their most urgent problems, in order to trace a plan of institutional goals to be pursued. This democratic environment of litigation resolution can be reached in the civil investigation – the most important tool to be used by the Public Attorney to fulfill its constitutional responsibilities. This requires the “processualization” of civil investigation, with the adoption of the adversary system, when it doesn‟t moot the investigations. Finally, was analyzed the dynamics of the civil investigation, in its phases of initiation, investigation and conclusion, with few comments about controversial issues that often arise during the extrajudicial investigations developed by the Public Attorney.